Materials’ properties of lightweight spiral hybrid CNT/epoxy composites enhanced reflection loss - Mohd Idris, Fadzidah (Semarak Ilmu Publishing, 2024)
Recently, various electronic devices have been developed to meet the requirements of higher frequency technology applications. This widely used application without realizing has created more electromagnetic interference pollution that is harmful to human health and other equipment. Therefore, more research interest focuses on fabricating the electromagnetic (EM) wave absorbing materials that can absorb the EM wave interference. In this regard, this research highlights the use of Iron Oxide and Cobalt Oxide as catalyst to synthesize hybrid CNT by using Thermal Vapor Deposition Tube (TVDT) method. The spiral hybrid CNT/epoxy composites were prepared at thickness of 1mm, 2mm and 3mm. The phase formation, microstructural, particle size and structural analysis of the hybrid CNT were analyzed by using X-ray diffractometer (XRD), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM) and RAMAN spectrometer respectively. The microwave characterization of the hybrid CNT/epoxy composite samples was analyzed by using Vector Network Analyzer (VNA) at GHz frequency range. The phase analysis confirmed the existence of Carbon and iron carbide in the sample. The microstructural of CNT formation are mostly in spiral and straight like structure. On the other hand, the structural analysis shows the sample are more towards defective structure with higher and broader D-band peak. This could enhance the EM wave absorption performance. The minimum reflection loss (RL) peak was ̴-23dB (t=3mm) obtained for all hybrid CNT composite samples. The differences of minimum reflection loss peak at different weight percentages are most likely shown by the shift of frequency range. Thus, this lightweight spiral hybrid CNT/epoxy composites results in better EM wave performance at different thin thickness used for different applications.